2013
DOI: 10.17532/jhsci.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 3 (TFF3) expression is regulated by insulin and glucose

Abstract: Introduction: Trefoil factors are effector molecules in gastrointestinal tract physiology. They are classified into three groups: the gastric peptides (TFF1), spasmolytic peptide (TFF2) and intestinal trefoil factor (TFF3). Previous studies have shown that trefoil factors are located and expressed in human endocrine pancreas suggesting that TFF3 play a role in: a) pancreatic cells migration, b) β-cell mitosis, and c) pancreatic cells regeneration. We speculated that the presence of TFF3 in pancreas, could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A previous study indicated that urinary TFF3 levels were decreased in patients with kidney tubular injury [32]. Another study indicated that serum TFF3 levels were influenced by insulin, glucose, and food intake [33]. Thus, serum TFF3 levels can be influenced by several factors besides tumor status.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that urinary TFF3 levels were decreased in patients with kidney tubular injury [32]. Another study indicated that serum TFF3 levels were influenced by insulin, glucose, and food intake [33]. Thus, serum TFF3 levels can be influenced by several factors besides tumor status.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the abundance of TFF3 found in HK-2 cell lysates: Western blot analysis of cell lysates confirmed the presence of TFF3 in lysates (Figure 1 E), implying the detection of an intracellular form of TFF3 ( 11 ). While it is known that TFF3 is regulated by HIF-1α ( 12 ), it is not known how hypoxic damage or the temporary withdrawal of insulin ( 13 ) might alter secretion of TFF3.…”
Section: Resultsmentioning
confidence: 99%
“…One example for this is diabetes mellitus type 1. Barrera Roa et al demonstrated that TFF3 expression is regulated by insulin and glucose [49]. Serum TFF3 levels are downregulated in serum of diabetes mellitus type 1 patients, and the presence of glucose and insulin results in elevated serum levels of TFF3.…”
Section: Discussionmentioning
confidence: 99%